Disability to Admit as a Change of Life after a Road Crash: Estimates and Related Factors in Benin for Prevention - GLELE AHANHANZO, YOLAINE; KPOZEHOUEN, ALPHONSE; DADDAH, DONATIEN; HOUNKPE DOS SANTOS, BELLA; SALAMI, Liamidhi; Paraiso, M. N. (My University, 2023)
Background: Disability is an underestimated issue in public health, with road crashes as leading cause. In Africa, motorcyclists disproportionately bear the burden of road crash injuries, including disability. To contribute to deci- sion-making for disability prevention, this study aims to determine the prevalence and factors associated with disability at 12 months among motor- cyclists involved in road crashes in Benin. Methods: This is a prospective, cross-sectional, analytical study based on 12-month follow-up data from a cohort of road crash victims set up in five hospitals in Benin. Data were col- lected from November 2020 to January 2021. Sample used for this analysis size was 297 motorcyclists. Disability was assessed using the Washington Group on Disabilities Statistics question set. Logistic regression analysis was used to identify risk factors for disability in victims 12 months after the crash. Results: The prevalence of disability was 12.5% 95% CI (9.2 - 16.7). Disability occurrence was associated with being over 45 years old (OR = 3.1; 95% CI = 1.5 - 6.6), severity of initial injury (OR = 3.3; 95% CI = 1.5 - 7.3) and hospi- talisation of the victim (OR = 6.9; 95% CI = 2.0 - 24). Conclusion: Age over 45 years, severity of initial injuries and hospitalisation of the victim were risk factors for the occurrence of disability among motorcyclists who were victims of road crashes in Benin. User awareness, law enforcement, holistic and early management of road crash victims could contribute to reducing the preva- lence of disability among victims in Benin.
Keywords: Disability; Motorcyclists; Road Traffic Accident